Prevention and Regression of Atherosclerosis: Emerging Treatments - Aliosvi Rodríguez Rodríguez; Gretchen Rodríguez Jaime (Revista Finlay)
Occlusive vascular diseases such as acute coronary syndrome, cerebral stroke, and peripheral arterial disease, represent a serious health problem worldwide. In recent decades, there has been significant progress in the diagnosis and treatment of atherosclerosis. Intravascular ultrasound imaging provides detailed information on the anatomy of the plaque and it has been used in several studies to evaluate the results. Atherosclerosis destabilizes the normal protective mechanism provided by the endothelium and this mechanism has been involved in the pathophysiology of acute coronary disease and brain stroke. Main efforts focus on prevention, especially at early ages. This paper is a review of 68 updated bibliographic citations in order to show the current options available for the prevention and reversal of the atherosclerotic process.